Problems of religious journalism in Kazakhstan - Байтенова, Нагима (Eurasian Journal of Religious Studies, 2017)
The article is devoted to problems of mass media in Kazakhstan, it reviewed the current state of the media, the main development trend, the main problems, the place and the role of media in society, the duality in shaping public opinion. The authors paid special attention to the main trends of religious journalism in Kazakhstan achievements in informing society about the current religious situation and problems existing in this sphere. The article particularly emphasizes that, along with certain achievements in the light of the religious situation in the country has enough problems in religious journalism.